The torture doctors. Human rights crimes and the road to justice.: by Steven. H. Miles. - Pérez-Sales, Pau (Torture Journal, 2021)
Book review The Torture Doctors. Human Rights Crimes and the Road to Justice. Steven. H. Miles. Georgetown University Press. 2020